Análisis de la propuesta fotográfica del cortometraje ecuatoriano Nuria de Piernas Largas - Armijos Granda, Ginger Micaela (2019)
Through this project the cinematographic experiences and the steps of photographic techniques are presented, being the production phase of great importance for its execution in the filming, where different concepts regarding compositions are made known; planes, angles, lighting, rule of thirds, colors etc. In addition, the history and evolution of photography is shown, in addition to this it refers to the main element of photography as light, since the result of the images will depend on this component such as its hue, clarity, and quality. The techniques that were applied for this project is the observation for its importance of knowing the characteristics and qualities that it demonstrates and the interview as research support to the director of photography Lcda. Dominique Pazmiño of the short film Nuria Long Legs, where he got to know the photographic techniques from the professional point of view since it refers to large international platforms Cannes Festival, Oxaca Film Fest, Vancouver Festival. The type of research is qualitative since its intention studies the phenomenon and raises indispensable questions of Why? How? and how? Exploratory research is based on elements that it has reaching analytical results